Sukuk Linked Waqf (An Analytical Study on the Development of a Productive Waqf Asset Management Model in Indonesia) - Qodri, Muhammad; Nurhayati, Immas; Huda, Nurul; Tanjung, Hendri (FKIP Universitas Jambi, 2026)
The This study aims to develop an integrated model of Sukuk-Linked Waqf to optimize unproductive waqf assets in Indonesia. Despite the vast potential of waqf assets, their utilization remains suboptimal due to limited managerial capacity, lack of innovation, and weak governance. This research adopts a qualitative approach combined with the Analytical Network Process (ANP) to identify key determinants influencing the effectiveness of waqf management. The results show that the consistency ratio (CR) values across stakeholders—Badan Wakaf Indonesia (0.08), Otoritas Jasa Keuangan (0.07), Dewan Syariah Nasional Majelis Ulama Indonesia (0.06), Bank Syariah Indonesia (0.09), investors (0.08), and practitioners (0.07)—are all below the acceptable threshold of 0.10, indicating reliable and consistent judgments. In terms of priority criteria, transparency (0.26) and regulatory support (0.22) are identified as the most influential factors, followed by public trust (0.20), institutional efficiency (0.18), and socialization or financial literacy (0.14). The study proposes an Integrated Sukuk–Waqf Synergy Model (ISWSM) as an innovative solution that integrates Islamic social finance and capital market instruments through a digital platform. The proposed model enables sustainable financing by combining philanthropic and commercial funds through a blended finance approach. This research contributes theoretically by enriching Islamic social finance literature and practically by offering an implementable model for stakeholders. It also provides policy implications for strengthening governance and developing innovative financing mechanisms to support sustainable socio-economic development.